Narrative therapies, psychology and the nature of empirical research. - Goncalves, Miguel M.; Salgado, Joao (Studia Psychologica: Theoria et praxis, 2006)
Narrative therapies assume themselves as an alternative movement to the traditional psychological models. Instead of insight, narrative appears as the main organizing concept of the therapeutic process. The main purpose of this kind of therapies is the deconstruction of taken for granted discourses that are perpetuating the problem. These therapies are known by their liberation efforts and even political positioning, representing an important innovation within this domain. However, they assume a hostile attitude against psychology that results in a lack of research of the therapeutic processes. In this article, we explore possible alternatives to this kind of rupture with psychology. In order to obtain a more specific picture of the actual situation, and borrowing from Valsiner, we present four different frames of reference of .doing psychology. (intra-individual, inter-individual, individual-ecological, and the individual socio-ecological). We consider that there are understandable reasons for a rejection of three of those frameworks. However, the individual social-ecological frame of reference seems to be a promising partner to a future dialogue between narrative therapies and research, since the cultural/semiotic dimensions are highlighted.